A treatise on health management - MOHAPATRA SC; Mohapatra, Meghkanta; Mohapatra, Vishwakant (Jaypee Brothers Medical Publishers (P) Ltd., 2016)
A textbook on health management for medical graduates, postgraduates, health sector program managers and implementers